Pricing strategy setting price levels, managing price discounts, & establishing price structures - Smith, Tim J. (Tim James) (South-Western Cengage Learning, 2012)
Emphasizes the stakeholder's importance in making decisions, highlighting key trade-offs to consider when choosing between opposing outcomes. This book presents quantitative instruction and qualitative concepts, helping you learn about the influences that should guide your decision making